An Introduction to the Dynamic Level of the Critical Pragmatic Arabic Approach (The International Journal for Scientific Research, 2026)
The research paper addresses the dynamic level of the Critical Pretextual Arabic Approach, which relies on the movement of language symbols, vocabulary, and their connotations. It also examines the extent of linguistic evasion between signifier and signified meanings in static linguistic fields within dynamic linguistic concepts. The scope of this paper is used to analyze the text's internal content and potential meaningful concepts, artistic, aesthetic, visual linguistic and behavioral structures. It also involves the movement of symbols, their significances, signifier, and signified meanings. This level of analysis includes static semantic and dynamic pragmatic domains, including the science of symbols and linguistic sciences; this level undertakes all the textual angles that the rest of the analytical pragmatic levels cannot reach. This level reaches them through dynamic balances related to the writer’s strategies and creativity. (CPAA) is used to analyze the text's internal content and artistic, aesthetic, visual linguistic, and behavioral structures.
Keywords: Internal Music; Context; Syntax; Literary Text; Dynamic Level